A circuitous route for in vitro multi-enzyme cascade production of cytidine triphosphate to overcome the thermodynamic bottleneck - Zonglin Li; Yahui Zhong; Zhoulei Qing; Zhimin Li (Bioresources and Bioprocessing, 2024)
Abstract Cytidine triphosphate (CTP), as a substance involved in the metabolism of phospholipids, proteins and nucleic acids, has precise drug effects and is a direct precursor for the synthesis of drugs such as citicoline. In this study, we established an in vitro six-enzyme cascade system to generate CTP. To avoid thermodynamic bottlenecks, we employed a circuitous and two-stage reaction strategy. Using cytidine as the key substrate, the final product CTP is obtained via the deamination and uridine phosphorylation pathways, relying on the irreversible reaction of cytidine triphosphate synthase to catalyze the amination of uridine triphosphate. Several extremophilic microbial-derived deaminases were screened and characterized, and a suitable cytidine deaminase was selected to match the first-stage reaction conditions. In addition, directed evolution modification of the rate-limiting enzyme CTP synthetase in the pathway yielded a variant that successfully relieved the product feedback inhibition, along with a 1.7-fold increase in activity over the wild type. After optimizing the reaction conditions, we finally carried out the catalytic reaction at an initial cytidine concentration of 20 mM, and the yield of CTP exceeded 82% within 10.0 h. Graphical Abstract